Road surface crack pouring material based on ST-BA copolymer modifier and preparation method

By using pavement seam filling materials based on ST-BA copolymer modifiers, the problems of poor bonding strength, insufficient ductile elasticity and poor weather resistance of existing hot seam filling materials are solved, and high bonding strength, good ductile elasticity and excellent durability are achieved, which is suitable for pavement crack repair in complex environments.

CN120082220APending Publication Date: 2025-06-03SHANXI RUITONG ROAD & BRIDGE NEW TECH CO LTD +2

Patent Information

Application Number
CN202510318698.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing hot seam filling materials have problems such as poor adhesion, insufficient elasticity, poor weather resistance, and harmful to the environment, making it difficult to effectively repair road cracks in complex environments.

Method used

The pavement seam filling materials based on ST-BA copolymer modifier are used to form seam filling materials with high adhesion, good elasticity and excellent durability by reasonably preparing matrix asphalt, ST-BA copolymer, modified fillers, tackifiers, compatible agents, stabilizers, anti-ultraviolet agents and adsorbents.

Benefits of technology

It realizes strong bonding between the seam filling materials and the crack wall, has excellent low-temperature and high-temperature performance, extends the service life, and reduces the release of harmful substances during construction, and meets environmental protection and energy-saving requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005316774520000081
    Figure BDA0005316774520000081
Patent Text Reader

Abstract

The invention belongs to the technical field of road maintenance, and particularly discloses a pavement crack pouring material based on an ST-BA copolymer modifier and a preparation method. The pavement crack pouring material based on the ST-BA copolymer modifier is prepared from the following components in parts by weight: 80 to 100 parts of matrix asphalt, 4 to 6 parts of ST-BA copolymer, 5 to 9 parts of modified filler, 3 to 9 parts of compatilizer, 2 to 5 parts of tackifier, 0.1 to 0.15 part of stabilizer, 1 to 5 parts of anti-ultraviolet agent and 1 to 5 parts of adsorbent. The crack pouring material prepared by the invention not only has physical and chemical compatibility with aggregate between cracks, but also has stronger cohesiveness with the aggregate, has better displacement capacity at low temperature, can resist the influence of external environmental conditions on the performance of the crack pouring material, and prolongs the service life of the crack pouring material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of highway maintenance, and particularly relates to a pavement crack filling material based on an ST-BA copolymer modifier and a preparation method thereof. Background Art

[0002] Asphalt concrete pavement is a widely used pavement type in China. With the increasing traffic load year by year, asphalt concrete pavement diseases are frequent, especially the crack problem. During the road use process, cracks will be aggravated by factors such as temperature, precipitation and load, and then develop into more serious diseases such as internal frost heaving and aggregate spalling, which damage the integrity of the road structure and reduce the service life of the road. Therefore, it is very important to repair cracks in time.

[0003] Currently, the commonly used crack filling materials can be divided into three types. One is hot-poured rubber asphalt, which is widely used because of its relatively low price and not demanding requirements for construction workers; the second is silicone resin. Since its viscosity is too high, it is not easy to fully penetrate into cracks, and it has high requirements for construction conditions, which is time-consuming and expensive, so it is mostly used for sealing joints of newly built concrete pavements; the third is cold-poured crack filling material, which is a crack filling material based on emulsified asphalt. It has fewer restricted conditions and does not need to be heated for use. It can be used on wet pavements and dusty walls, and has little influence on the repair performance of dust and moisture. However, its failure rate is relatively high during long-term service. Through comprehensive comparison, using heating-type crack filling materials to fill cracks is the most effective way to treat cracks. The crack filling materials effectively prevent surface water and sundries from entering the pavement structure in a sealing form, and to a certain extent restore the bearing capacity of the pavement. However, the existing hot-poured crack filling materials have the following problems: (1) Most of the crack filling materials are modified asphalt, and the commonly used modifiers are SBS, polyurethane, PE, rubber powder, SBR, etc. The SBS modifier has limitations in improving the elongation and elasticity of the crack filling material, and its storage stability is poor; although SBR modified asphalt has good ductility, its resistance to deformation force is poor; polyurethane, PE, and rubber powder modified asphalt have excellent high-temperature performance, but poor low-temperature improvement effect; (2) The adhesion to cracks is poor, and it is easy to be taken away under the repeated rolling of vehicle tires after crack filling; (3) The toughness and elasticity are poor. In low-temperature climate conditions, the elasticity and ductility are poor and it is easy to crack; (4) The durability is poor. When exposed to the air for a long time, it is severely damaged by ultraviolet aging; (5) Harmful fumes are released during heating in the use process, which endangers the health of operators.

[0004] Therefore, it is necessary to find a new type of asphalt modifier with good low-temperature crack resistance and without sacrificing high-temperature performance. And it is very important to prepare a high-performance heating-type crack filling material with high adhesion, high elongation and elasticity, good aging resistance and environmental protection for the popularization and application of crack filling materials and the crack treatment of roads. At the same time, it has great significance for promoting the development of the road maintenance industry in China. Summary of the Invention

[0005] In view of the problems existing in the existing crack filling materials, such as poor adhesion, insufficient elongation elasticity, poor weather resistance, and harm to the environment, the present invention aims to provide a pavement crack filling material based on an ST-BA copolymer modifier and a preparation method thereof. This crack filling material not only has physical and chemical compatibility with the aggregates in the cracks, but also has strong adhesion to the aggregates, has good displacement ability at low temperatures, can resist the influence of external environmental conditions on its performance, extends the service life of the crack filling material, and in addition, can reduce the release of harmful substances during the construction operation process.

[0006] The object of the present invention is achieved by the following technical solutions:

[0007] A pavement crack filling material based on an ST-BA copolymer modifier, by weight, the preparation of the pavement crack filling material includes the following components: 80-100 parts of matrix asphalt, 4-6 parts of ST-BA copolymer;

[0008] Further, in order to increase the toughness and strength of the crack filling material, the preparation of the pavement crack filling material further includes the following components: 5-9 parts of modified filler;

[0009] Further, in order to increase the interfacial adhesion performance of the crack filling material, the preparation of the pavement crack filling material further includes the following components: 2-5 parts of tackifier;

[0010] Furthermore, the preparation of the pavement crack filling material further includes components: 3-9 parts of compatibilizer;

[0011] Furthermore, the preparation of the pavement crack filling material further includes components: 0.1-0.15 parts of stabilizer;

[0012] Furthermore, the preparation of the pavement crack filling material further includes components: 1-5 parts of ultraviolet absorber;

[0013] Furthermore, the preparation of the pavement crack filling material further includes components: 1-5 parts of adsorbent.

[0014] Most preferably, a pavement crack filling material based on an ST-BA copolymer modifier, by weight, the preparation of the pavement crack filling material includes the following components: 80-100 parts of matrix asphalt, 4-6 parts of ST-BA copolymer, 5-9 parts of modified filler, 3-9 parts of compatibilizer, 2-5 parts of tackifier, 0.1-0.15 parts of stabilizer, 1-5 parts of ultraviolet absorber and 1-5 parts of adsorbent.

[0015] Further, the matrix asphalt is petroleum asphalt, selected from one or several of 70# asphalt, 90# asphalt, and 110# asphalt.

[0016] Further, the ST-BA copolymer is obtained by copolymerizing butyl acrylate (BA) and styrene (ST) monomers in a mass ratio of 8:2.

[0017] Further, the ST-BA copolymer is obtained by reacting at a constant temperature of 80 ± 5 °C for 5 h in a water bath under an inert gas condition with azobisisobutyronitrile (AIBN) as an initiator and cyclohexane as an organic solvent. Among them, the mass of the initiator accounts for 0.05% - 0.10% of the total mass of the copolymer monomers, and the mass of the organic solvent is 1.1 - 1.2 times the total mass of the copolymer monomers.

[0018] Further, the copolymerization reaction for synthesizing the ST-BA copolymer is carried out under stirring, and the stirring rate is 200 - 300 r / min.

[0019] Further, the modified filler is a recycled powder filler modified by a modifier. The recycled powder filler is one or more of limestone powder, marble powder, talc powder, and calcium carbonate powder. The particle size of the recycled powder filler is 40 - 200 mesh. The modifier is one or more of silane coupling agents KH550, KH560, KH570, polyphosphoric acid, maleic anhydride, or acetic anhydride. The modification method is the impregnation method.

[0020] Further, the preparation of the modified filler includes: mixing an ethanol solution and a modifier, stirring evenly, and standing for 10 - 30 min to obtain a modifier solution with a concentration of 10 wt% - 20 wt%; adding 10 wt% - 20 wt% of the recycled powder filler based on the mass of the modifier solution to the modifier solution, fully stirring and then standing for 1 - 3 h to obtain a mixed solution; drying the mixed solution to obtain the modified filler. Among them, the ethanol solution can be obtained by mixing 30 - 50 parts of absolute ethanol and 10 - 15 parts of water.

[0021] Further, the compatibilizer is one or more of petroleum-based rubber oils.

[0022] Further, the tackifier is one or more of poly-a-methylstyrene resin, xylene formaldehyde resin, cashew oil-modified phenolic resin, and terpene phenolic resin.

[0023] Further, the stabilizer is one or more of sulfur, ethylene propylene diene monomer rubber, cis-1,4-polybutadiene rubber, and butyl rubber.

[0024] Further, the ultraviolet absorber is one or more of zinc oxide, iron oxide red, carbon black, ultraviolet absorber UV530, ultraviolet absorber UV531, and ultraviolet absorber UV234.

[0025] Further, the adsorbent is one or more of silica, activated carbon, calcium silicate, diatomaceous earth, and kaolin, and the particle size of the adsorbent is 200-600 mesh.

[0026] A preparation method of a pavement joint sealing material based on an ST-BA copolymer modifier includes the following steps:

[0027] (1) Heat the base asphalt to 170-180°C, add the ST-BA copolymer and the compatibilizer to the base asphalt, keep the temperature unchanged, stir and swell at a speed of 300-800 r / min for 20-30 min, and then add the tackifier and continue stirring for 30-60 min;

[0028] (2) Then cool down to 140-160°C and add the stabilizer, keep the constant temperature, and wait for it to react for 10 min-20 min;

[0029] (3) Lower the temperature to 120°C-140°C, stir and add the modified filler at a speed of 80-120 r / min, continue stirring until there are no lumps, then successively add the anti-ultraviolet agent and the adsorbent, and stir evenly to obtain the joint sealing material.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] 1) Super strong adhesion, and the interface is firmly combined. The joint sealing material has good fluidity at 150°C and can fully penetrate into the pores of the crack to form a strong anchoring structure. The unsaturated bonds and aldehyde groups in the tackifier will cross-link with the components in the asphalt, and the benzene ring will undergo substitution or addition reactions with some oxygen-containing, sulfur-containing or nitrogen-containing compounds in the asphalt to form a more stable network structure, which enhances the adhesion between the joint sealing material and the aggregate in the crack wall and avoids the cracking of the joint sealing material and the crack interface.

[0032] 2) High elongation elasticity, not brittle at low temperature, and no displacement at high temperature. The incorporation of the ST-BA copolymer with a specific ratio of soft and hard segments in the joint sealing material makes the joint sealing material have excellent cold resistance and high elongation elastic ability. It can maintain good ductility at -20°C, is not easy to crack, and changes with the change of the crack; at the same time, it has good high-temperature performance, does not flow and displace in a high-temperature environment, and can meet the maintenance operation requirements of the road in a complex environment.

[0033] 3) Excellent durability. The addition of the modified filler in the joint sealing material increases the toughness and strength of the joint sealing material, and can well resist the embedding of other substances such as foreign stone chips and impurities. In addition, this joint sealing material can effectively prevent ultraviolet aging when exposed to the air for a long time, and has excellent durability.

[0034] 4) Environmentally friendly and energy-saving. The filler used in this invention is recycled powder after modification, achieving the recycling and application of waste. At the same time, the addition of the adsorbent adsorbs harmful substances after the heating of the joint filling material, reducing the emission of harmful substances. This invention conforms to the new concept of environmental protection and energy saving in the construction industry. Detailed implementation manners

[0035] To better understand the present invention, the content of the present invention will be further clarified below in conjunction with embodiments. However, the content claimed in the claims of the present invention is not limited to the following embodiments.

[0036] In the following Examples 1-4, the ST-BA copolymer used was prepared as follows: 250 g of butyl acrylate (BA), 62.5 g of styrene (ST), 0.2 g of azobisisobutyronitrile (AIBN) and 350 g of cyclohexane were added to a 500 mL three-necked flask; stirring was started, the stirring speed was 300 r / min, and a constant temperature water bath was used for heating. Under the condition of inert gas nitrogen, the reaction was carried out at a constant temperature of 80 °C for 5 h; after the reaction was completed, the reaction product was poured into a clean container, washed repeatedly with petroleum ether, and then placed in a vacuum drying oven and dried at 65 °C for about 5 h until the mass no longer changed to obtain the ST-BA copolymer.

[0037] In the following Comparative Example 4, the ST-BA copolymer used was prepared as follows: 187.5 g of butyl acrylate (BA), 125 g of styrene (ST), 0.2 g of azobisisobutyronitrile (AIBN) and 350 g of cyclohexane were added to a 500 mL three-necked flask; stirring was started, the stirring speed was 300 r / min, and a constant temperature water bath was used for heating. Under the condition of inert gas nitrogen, the reaction was carried out at a constant temperature of 80 °C for 5 h; after the reaction was completed, the reaction product was poured into a clean container, washed repeatedly with petroleum ether, and then placed in a vacuum drying oven and dried at 65 °C for about 5 h until the mass no longer changed to obtain the ST-BA copolymer.

[0038] In the following examples, the limestone powder used was from the mixing station of Yuci Branch of Shanxi Transportation Maintenance, with a particle size of 80 mesh; the marble powder used was from Suizhou Wanlei Stone Industry Co., Ltd., with a particle size of 100 mesh; the talc powder used was from Anhui Xuanlang New Material Technology Co., Ltd., with a particle size of 200 mesh; the calcium carbonate powder used was from Hebei Guanghui Industry Co., Ltd., with a particle size of 40 mesh.

[0039] Example 1 A preparation method of a pavement joint filling material based on an ST-BA copolymer modifier, comprising the following steps:

[0040] (1) Preparation of modified limestone powder: Weigh 300 g of absolute ethanol, 150 g of deionized water and 50 g of silane coupling agent KH550, mix them evenly, let stand for 30 min to obtain a modified solution; then add 60 g of limestone powder into the modified solution, stir evenly and let stand for 2 h to obtain a mixture; finally, put the mixture into an oven and dry it at 105 °C for 4 h to obtain modified limestone powder.

[0041] (2) By weight, weigh 80 parts of 70# asphalt, 6 parts of ST-BA copolymer, 8 parts of modified limestone powder, 4 parts of aromatic-based rubber oil 3# oil, 3 parts of poly-a-methylstyrene resin, 0.1 part of sulfur, 3 parts of zinc oxide, and 2 parts of silica (200 mesh).

[0042] (3) Heat the base asphalt to 170 °C, add the ST-BA copolymer and aromatic-based rubber oil 3# oil to the base asphalt, keep the temperature unchanged, stir and swell at a speed of 300 r / min for 30 min, and then add the poly-a-methylstyrene resin and continue stirring for 40 min.

[0043] (4) Then cool down to 160 °C and add sulfur, keep the constant temperature, and wait for it to react for 20 min.

[0044] (5) Lower the temperature to 120 °C, lower the rotation speed to 80 r / min and stir, add the modified limestone powder, continue stirring until there are no lumps, then successively add zinc oxide and silica, stir evenly to obtain a crack-sealing material. Example 2 A preparation method of a pavement crack-sealing material based on an ST-BA copolymer modifier, comprising the following steps:

[0045] (1) Preparation of modified marble powder: Weigh 500 g of absolute ethanol, 100 g of deionized water and 72 g of silane coupling agent KH560, mix them evenly, let stand for 10 min to obtain a modified solution; then add 80 g of marble powder into the modified solution, stir evenly and let stand for 1 h to obtain a mixture; finally, put the mixture into an oven and dry it at 105 °C for 4 h to obtain modified marble powder.

[0046] (2) By weight, weigh 80 parts of 90# asphalt, 6 parts of ST-BA copolymer, 5 parts of modified marble powder, 3 parts of naphthenic oil rubber oil K6B, 4 parts of xylene formaldehyde resin, 0.15 part of ethylene propylene diene monomer rubber, 3 parts of ultraviolet absorber UV530, and 5 parts of activated carbon (200 mesh).

[0047] (3) First, heat the base asphalt to 170 °C, add the ST-BA copolymer and naphthenic oil rubber oil K6B to the base asphalt, keep the temperature unchanged, stir and swell at a speed of 600 r / min for 20 min, and then add the xylene formaldehyde resin and continue stirring for 60 min.

[0048] After that, cool down to 150 °C and add ethylene propylene diene monomer rubber, keep the temperature constant and wait for it to react for 20 min.

[0049] (5) Lower the temperature to 140 °C, lower the rotation speed to 100 r / min and stir, add modified marble powder, continue stirring until there are no lumps, then add ultraviolet absorber UV530 and activated carbon successively, and obtain the crack filling material after stirring evenly.

[0050] Example 3 A preparation method of a pavement crack filling material based on an ST-BA copolymer modifier, comprising the following steps:

[0051] (1) Prepare modified talcum powder: Weigh 300 g of absolute ethanol, 150 deionized water and 60 g of silane coupling agent KH570, mix and stir evenly, let stand for 20 min to obtain a modified solution; then add 80 g of talcum powder to the modified solution, stir evenly, and let stand for 3 h to obtain a mixed solution; finally, put the mixed solution into an oven and dry at 105 °C for 4 h to obtain modified talcum powder.

[0052] (2) Weigh 90 parts of 70# asphalt, 6 parts of ST-BA copolymer, 9 parts of modified talcum powder, 6 parts of paraffin oil S500 rubber oil, 3 parts of terpene phenolic resin, 0.15 parts of butyl rubber, 4 parts of ultraviolet absorber UV234, and 5 parts of diatomite (200 mesh) respectively by weight.

[0053] (3) First, heat the base asphalt to 180 °C, add the ST-BA copolymer and paraffin oil S500 rubber oil to the base asphalt, keep the temperature unchanged, stir and swell at a rotation speed of 800 r / min for 30 min, and then add the terpene phenolic resin and continue stirring for 40 min.

[0054] (4) After that, cool down to 160 °C and add butyl rubber, keep the temperature constant and wait for it to react for 15 min.

[0055] (5) Lower the temperature to 120 °C, lower the rotation speed to 100 r / min and stir, add modified talcum powder, continue stirring until there are no lumps, then add ultraviolet absorber UV234 and diatomite successively, and obtain the crack filling material after stirring evenly.

[0056] Example 4 A preparation method of a pavement crack filling material based on an ST-BA copolymer modifier, comprising the following steps:

[0057] (1) Prepare modified calcium carbonate powder: Weigh 500 g of absolute ethanol, 100 g of deionized water and 80 g of maleic anhydride, mix and stir evenly, let stand for 30 min to obtain a modified solution; then add 90 g of calcium carbonate powder to the modified solution, stir evenly, and let stand for 2 h to obtain a mixed solution; finally, put the mixed solution into an oven and dry at 105 °C for 4 h to obtain modified calcium carbonate powder.

[0058] (2) Weigh 80 parts of 70# asphalt, 5 parts of ST-BA copolymer, 8 parts of modified calcium carbonate powder, 5 parts of aromatic rubber oil (5# oil), 4 parts of terpene phenolic resin, 0.1 part of sulfur, 4 parts of iron oxide red, and 5 parts of kaolin (200 mesh) respectively by weight.

[0059] (3) First, heat the base asphalt to 180°C. Add the ST-BA copolymer and aromatic rubber oil (5# oil) to the base asphalt, keep the temperature unchanged, stir and swell at a speed of 500 r / min for 25 min, and then add the terpene phenolic resin and continue stirring for 50 min.

[0060] (4) Then cool down to 140°C and add sulfur, keep the temperature constant, and wait for it to react for 20 min.

[0061] (5) Lower the temperature to 120°C, lower the rotation speed to 100 r / min and stir, add the modified calcium carbonate powder, continue stirring until there are no lumps, then add iron oxide red and kaolin successively, and stir evenly to obtain the crack filling material.

[0062] Comparative Example 1

[0063] Compared with Example 1, in Comparative Example 1, only the modifier ST-BA copolymer component was replaced with Sinopec Baling Petrochemical linear SBS modifier (YH 791H) to prepare the crack filling material.

[0064] Comparative Example 2

[0065] Compared with Example 2, in Comparative Example 2, only the tackifier xylene formaldehyde resin component was not added to prepare the crack filling material.

[0066] Comparative Example 3

[0067] Compared with Example 3, in Comparative Example 3, only the filler modified talc powder component was replaced with unmodified talc powder to prepare the crack filling material.

[0068] Comparative Example 4

[0069] Compared with Example 4, in Comparative Example 4, only the modifier ST-BA copolymer component was replaced with the ST-BA copolymer synthesized from soft monomer (BA) and hard monomer (ST) in a mass ratio of 6:4 to prepare the crack filling material.

[0070] According to the specifications of "Pavement Heating-Type Sealant" (JT / T 740-2015) and "Sealant for Road and Bridge Joints" (JT / T 976-2005), the performance of the crack filling materials prepared in Examples 1-4 and Comparative Examples 1-4 was tested, and the test results are shown in Table 1.

[0071] Table 1 Test Results of the Performance of Crack Filling Materials

[0072]

[0073] Combined with the data in Table 1, it can be seen from the comparison between Example 1 and Comparative Example 1 that, compared with SBS as an asphalt modifier, the ST-BA copolymer can significantly improve the high-temperature performance of the crack-sealing material (higher softening point), is not prone to flow under high-temperature environments (smaller flow value), and has good elongation elasticity under low-temperature conditions (higher elastic recovery rate).

[0074] It can be seen from the comparison between Example 2 and Comparative Example 2 that the addition of the tackifier can improve the high-temperature performance of the crack-sealing material and increase the bonding performance at the interface.

[0075] It can be seen from the comparison between Example 3 and Comparative Example 3 that for the crack-sealing material with unmodified talc powder directly used as a filler, the penetration is relatively high. After adding talc powder with modified surface, the toughness and strength of the crack-sealing material are increased, and it can well resist the embedding of other substances such as foreign stone chips and impurities.

[0076] It can be seen from the comparison between Example 4 and Comparative Example 4 that the mass ratio of the soft monomer (BA) to the hard monomer (ST) in the ST-BA copolymer component of the modifier added to the crack-sealing material should not be too low (such as 6:4), otherwise the performance of the crack-sealing material will decrease significantly, the softening point is relatively low, it is extremely prone to flow at high temperatures, the elongation elasticity of the crack-sealing material is poor under low-temperature conditions, it fails the low-temperature tensile test, and its bonding property with the medium is relatively low (it fails the specified elongation adhesion test), and the overall performance is worse than that of the conventional asphalt modifier SBS. In addition, the inventor further increased the mass ratio of the soft monomer (BA) to the hard monomer (ST) in the ST-BA copolymer component of the modifier added to the crack-sealing material to 7:3. The low-temperature tensile performance of the crack-sealing material passed, and the elastic recovery rate also increased. However, the fluidity of the crack-sealing material is poor, and its bonding property with the medium has not been improved yet.

Claims

1. A pavement crack filling material based on ST-BA copolymer modifier, characterized in that: The pavement crack filling material comprises the following components by weight: 80 to 100 parts of base asphalt and 4 to 6 parts of ST-BA copolymer; The ST-BA copolymer is obtained by copolymerizing butyl acrylate BA and styrene ST monomers in a mass ratio of 8:

2.

2. The pavement crack filling material based on ST-BA copolymer modifier according to claim 1, characterized in that: The ST-BA copolymer is obtained by using azobisisobutyronitrile as an initiator and cyclohexane as an organic solvent in an inert gas environment in a constant temperature water bath at 80±5°C for 5 hours. Preferably, the mass of the initiator accounts for 0.05%-0.10% of the total mass of the copolymer monomers, and the mass of the organic solvent is 1.1-1.2 times the total mass of the copolymer monomers; Preferably, the copolymerization reaction for synthesizing the ST-BA copolymer is carried out under stirring at a stirring rate of 200-300 r / min.

3. The pavement crack filling material based on ST-BA copolymer modifier according to claim 1, characterized in that: The preparation of the pavement crack filling material also includes the following components: 5 to 9 parts of modified filler; The modified filler is a recycled powder filler modified by a modifier, the recycled powder filler is one or more of limestone powder, marble powder, talcum powder, and calcium carbonate powder, the particle size of the recycled powder filler is 40-200 meshes, the modifier is one or more of silane coupling agent KH550, KH560, KH570, polyphosphoric acid, maleic anhydride, and acetic anhydride, and the modification method is an impregnation method.

4. The pavement crack filling material based on ST-BA copolymer modifier according to claim 3, characterized in that: The preparation of the modified filler includes: taking an ethanol solution and a modifier, mixing them, stirring them evenly, and standing them for 10 to 30 minutes to obtain a modifier solution with a concentration of 10wt% to 20wt%; taking 10wt% to 20wt% of the mass of the modifier solution, adding the recovered powder filler to the modifier solution, stirring it fully, and standing it for 1-3 hours to obtain a mixed solution; drying the mixed solution to obtain the modified filler; preferably, the ethanol solution is obtained by mixing 30 to 50 parts of anhydrous ethanol with 10 to 15 parts of water.

5. The pavement crack filling material based on ST-BA copolymer modifier according to claim 3, characterized in that: The preparation of the pavement crack filling material also includes the following components: 2 to 5 parts of a tackifier; The tackifier is one or more of poly-a-methylstyrene resin, xylene formaldehyde resin, cashew nut oil modified phenolic resin, and terpene phenolic resin.

6. The pavement crack filling material based on ST-BA copolymer modifier according to claim 5, characterized in that: The preparation of the pavement crack filling material also includes the following components: 3 to 9 parts of a compatibilizer; The compatibilizer is one or more of petroleum-based rubber oils; The base asphalt is petroleum asphalt.

7. The pavement crack filling material based on ST-BA copolymer modifier according to claim 6, characterized in that: The preparation of the pavement caulking material also includes the following components: 0.1 to 0.15 parts of a stabilizer, 1 to 5 parts of an anti-ultraviolet agent, and 1 to 5 parts of an adsorbent.

8. The pavement crack filling material based on ST-BA copolymer modifier according to claim 7, characterized in that: The stabilizer is one or more of sulfur, EPDM rubber, butadiene rubber, and butyl rubber; The anti-ultraviolet agent is one or more of zinc oxide, red iron oxide, carbon black, anti-ultraviolet agent UV530, anti-ultraviolet agent UV531, and anti-ultraviolet agent UV234; The adsorbent is one or more of silicon dioxide, activated carbon, calcium silicate, diatomaceous earth and kaolin, and the particle size of the adsorbent is 200-600 meshes.

9. The method for preparing a pavement crack-filling material based on a ST-BA copolymer modifier according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) heating the base asphalt to 170-180° C., adding the ST-BA copolymer and the compatibilizer described in any one of claims 1-8 to the base asphalt, maintaining the temperature unchanged, stirring and swelling at a speed of 300-800 r / min for 20-30 min, adding the tackifier and continuing stirring for 30-60 min; (2) Then cool to 140-160°C, add stabilizer, maintain constant temperature, and allow to react for 10-20 minutes; (3) Lower the temperature to 120°C to 140°C, add the modified filler with stirring at a speed of 80 to 120 r / min, continue stirring until there are no lumps, then add the anti-ultraviolet agent and adsorbent in succession, and stir evenly to obtain the caulking material.

Citation Information

Patent Citations

  • High efficiency resin fissures cementation glue and preparation thereof

    CN101838510A

  • Pavement seam filling material

    CN101935459A

  • High-viscosity modified crack pouring adhesive material for bituminous pavement and preparation method

    CN107722927A

  • Environment-friendly crack pouring adhesive and preparation method thereof

    CN113773801A

  • High-temperature pavement crack pouring adhesive and preparation method thereof

    CN119351053A

Cited By

  • Normal-temperature bio-based asphalt cold patch material and preparation method thereof

    CN121044836A